PENGEMBANGAN MEDIA PEMBELAJARAN SAINS TERHADAP PERKEMBANGAN KOGNITIF ANAK USIA 5-6 TAHUN - Anita Roslina Simanjuntak; Jane Koswojo; Sindy Anugerah Wati (CERIA (Cerdas Energik Responsif Inovatif Adaptif), 2022)
This study aims to create and develop science learning media that can be used to stimulate aspects of cognitive development of children aged 5-6 years to help educators to convey material so that children also more easily understand the material presented by educators. The research was carried out on children aged 5-6 years in the even semester of the 2021/2022 academic year. Learning media is made in the form of Children's Worksheets (LKA), in which there are various science experiment activities for children aged 5-6 years. The type of research used is research and development (R and D), the research model used is the ADDIE research model (Analysis, Design, Development, Implementation, and Evaluation) which was adapted from Branch. The data collection techniques used were observation and questionnaires to determine the development of early childhood science learning media. Data analysis used effectiveness data analysis to determine the effectiveness of using science learning worksheets as stimulation of cognitive development aspects. The results of the effectiveness of using the development of science learning worksheets in 12 children obtained an average score of 87%. The score results are included in the "very good" category. Based on the results of the effectiveness of using the LKA for science learning, the provision of LKA for science learning is effective in stimulating the cognitive development of children aged 5-6 years.PPenelitian ini bertujuan untuk membuat dan mengembangkan media pembelajaran sains yang dapat digunakan untuk menstimulasi aspek perkembangan kognitif anak usia 5-6 tahun sehingga membantu pendidik untuk menyampaikan materi agar anak juga lebih mudah memahami materi yang disampaikan oleh pendidik. Penelitian dilaksanakan pada anak usia 5-6 tahun di semester genap tahun ajaran 2021/2022. Media pembelajaran dibuat dalam bentuk Lembar Kerja Anak (LKA), dimana didalamnya terdapat berbagai kegiatan eksperimen sains untuk anak usia 5-6 tahun. Jenis penelitian yang digunakan adalah research and development (R and D), model penelitian yang digunakan yaitu model penelitian ADDIE (Analysis, Design, Development, Implementation, and Evaluation) yang diadaptasi dari Branch. Teknik pengumpulan data yang digunakan yaitu pengamatan (observasi) dan pemberian angket (kuesioner) untuk mengetahui pengembangan media pembelajaran sains anak usia dini. Analisis data menggunakan analisis data keefektifan  untuk mengetahui efektivitas penggunaan LKA pembelajaran sains sebagai stimulasi aspek perkembangankognitif. Hasil efektivitas penggunaan pengembangan LKA pembelajaran sains pada 12 anak memperoleh rata-rata skor 87%. Hasil skor tersebut termasuk dalam kategori “sangat baik”. Berdasarkan hasil efektivitas penggunaan LKA pembelajaran sains tersebut, maka pemberian LKA pembelajaran sains efektif untuk menstimulasi perkembangan kognitif anak usia 5-6 tahun.